Quartet [videorecording (DVD)] - Hoffman, Dustin, 1937-; Smith, Maggie, 1934-; Connolly, Billy; Courtenay, Tom; Collins, Pauline, 1940-; Gambon, Michael (Anchor Bay Entertainment, 2013)
The rumor circling the halls is that Beecham House (the home for retired musicians) is soon to play host to a new resident. Word is, it's a star. Reginald, Wilfred and Cecily are in for a special shock when the new arrival turns out to be none other than their former singing partner, Jean. Her subsequent career as a star soloist, and the ego that accompanied it, split up their long friendship and ended her marriage to Reggie, who takes the news of her arrival particularly hard.